2012
DOI: 10.3109/09553002.2013.734943
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin reduces X-ray radiation-induced lung injury in mice by modulating oxidative stress and cytokine expression

Abstract: The present results suggest that melatonin reduces radiation-induced lung injury via a significant reduction of oxidative stress and of the production of cytokines, such as TGF-β1 and TNF-α, the production of which increased following lung irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 37 publications
1
32
0
4
Order By: Relevance
“…Jang et al (2013)have shown that the administration of melatonin before lung irradiation ameliorates the upregulation of TNF-α, TGF-β, and IL-6. Also, they showed an increase in SOD and catalase activity and GSH levels, and a reduction of oxidative damage in lung tissue compared to irradiation only (Jang et al 2013). TGF-β has a suppressive effect on SOD and catalase gene expression.…”
Section: Effect Of Melatonin On Cytokines Production Following Irradimentioning
confidence: 99%
See 1 more Smart Citation
“…Jang et al (2013)have shown that the administration of melatonin before lung irradiation ameliorates the upregulation of TNF-α, TGF-β, and IL-6. Also, they showed an increase in SOD and catalase activity and GSH levels, and a reduction of oxidative damage in lung tissue compared to irradiation only (Jang et al 2013). TGF-β has a suppressive effect on SOD and catalase gene expression.…”
Section: Effect Of Melatonin On Cytokines Production Following Irradimentioning
confidence: 99%
“…Thus, melatonin, through these pathways, may reduce both acute and chronic consequences caused by inflammation following radiotherapy (Bondy et al 2004). Jang et al (2013)have shown that the administration of melatonin before lung irradiation ameliorates the upregulation of TNF-α, TGF-β, and IL-6. Also, they showed an increase in SOD and catalase activity and GSH levels, and a reduction of oxidative damage in lung tissue compared to irradiation only (Jang et al 2013).…”
Section: Effect Of Melatonin On Cytokines Production Following Irradimentioning
confidence: 99%
“…In addition to neutralizing ROS species, Mel also acts via the stimulation of various anti-oxidative systems and stabilizes cell membranes (19). As such, Mel modulates the gene expression levels of numerous protective enzymes to reduce apoptosis and lipid peroxidation (20,21). Mel has previously been demonstrated to improve the survival rates of mice when administered prior to irradiation exposure (22).…”
Section: Introductionmentioning
confidence: 99%
“…Entre os modelos animais atualmente utilizados, tem-se observado uma resposta adequada à indução de dislipidemia e inflamação, porém elevada resistência à indução de estresse oxidativo. Essa limitação metodológica tem sido superada através de intervenções mais agressivas e muitas vezes sem correspondência com o modelo humano, tais como exposição à radiação, aplicação de tetracloreto de carbono (CCl 4 ) e manipulação genética como os animais knockouts para as enzimas atioxidantes (Nomura e Yamaoka, 1999;Cooper et al, 2002;Kunitomo et al, 2009;Zhang et al, 2009;Chew et al, 2010;Sakata et al, 2012;Jang et al, 2013;Laher et al, 2013).…”
Section: Introductionunclassified
“…As formas de indução do estresse oxidativo são mais complexas, incluindo exposição à radiação, administração de CCl 4 , aplicação de estreptozotocina para indução de diabetes, exposição excessiva à poluentes ou fumaça de cigarro, exercício físico extenuante, ou uso de animais transgênicos ou "knockout" para enzimas antioxidantes (Nomura e Yamaoka, 1999;Cooper et al, 2002;Kunitomo et al, 2009;Zhang et al, 2009;Chew et al, 2010;Sakata et al, 2012;Jang et al, 2013;Laher et al, 2013 (Sentman et al, 2006).…”
Section: Introductionunclassified